2005
DOI: 10.1590/s0021-75572005000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anticorpos contra o vírus da hepatite A em crianças e adolescentes expostos e/ou infectados pelo HIV

Abstract: Objective: To evaluate the prevalence of hepatitis A virus antibodies in HIV-exposed and/or HIV-infected children and adolescents.Methods: Between September 1996 and August 2002, 352 patients (200 exposed, but not HIV-infected and 152 HIV exposed and infected) were included in this study. These children and adolescents (age ranged between 1 and 14 years) were all followed up at the Pediatric AIDS Clinic of the Federal University of São Paulo (UNIFESP) and had anti-HAV antibodies determined by a commercially av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…Until recently, it was claimed that there was no consistent evidence of exacerbated acute liver disease due to HAV in patients with HIV. Gouvêa et al 1 present a succinct review of the literature together with interesting data from their own study which demonstrate the relevance of the association between HIV and HAV. They performed a retrospective analysis of the medical records of 352 patients receiving outpatients treatment at the Pediatric Infectology Department Clinic at the UNIFESP/EPM, in São Paulo.…”
Section: See Related Article On Page 205mentioning
confidence: 98%
See 1 more Smart Citation
“…Until recently, it was claimed that there was no consistent evidence of exacerbated acute liver disease due to HAV in patients with HIV. Gouvêa et al 1 present a succinct review of the literature together with interesting data from their own study which demonstrate the relevance of the association between HIV and HAV. They performed a retrospective analysis of the medical records of 352 patients receiving outpatients treatment at the Pediatric Infectology Department Clinic at the UNIFESP/EPM, in São Paulo.…”
Section: See Related Article On Page 205mentioning
confidence: 98%
“…There was a greater prevalence of total HAV antibodies in the HIV group for all age groups and no association was observed between immunological category and the presence of HAV antibodies. 1 Despite the decline in HAV incidence over recent years in certain Latin American countries, there are still high rates of disease and even occasional epidemics, indicating that HAV remains an important Public health problem in our country. 2 Studies of pediatric HIV patients response to hepatitis A vaccination are very rare.…”
Section: See Related Article On Page 205mentioning
confidence: 99%
“…Pesquisa realizada na UNIFESP com crianças e adolescentes expostos ao HIV revelou que a prevalência de indivíduos suscetíveis à hepatite A entre adolescentes é maior do que na população de não infectados 48 e que a vacina é segura e eficaz, protegendo 100% das crianças infectadas (sem imunossupressão grave) vacinadas 49 . Considerando-se que as crianças com AIDS recebem terapia antiretroviral que é potencialmente hepatotóxica e que a infecção pelo vírus da Hepatite A poderia agravar a infecção pelo HIV, a profilaxia vacinal é importante para esse grupo de pacientes.…”
Section: Crianças Adolescentes E Adultos Infectados Pelo Hivunclassified
“…31,40 In Brazil, the hepatitis A vaccine is not available to all HIV-infected children; it must be applied to susceptible individuals who present with hepatopathy in a two-dose schedule with an interval of 6 months between them. 40 Research conducted at UNIFESP with children and adolescents exposed to HIV revealed that the prevalence of individuals susceptible to hepatitis A among adolescents is greater than in the non-infected population 48 and that the vaccine is safe and efficient, protecting 100% of the vaccinated HIV-infected children (without severe immunosuppression). 49 Considering that children with Here we shall deal with the infectious diseases for which the use of vaccines may prevent infection and the disease, even after exposure.…”
Section: Vaccination Of the Child Receiving Corticosteroid Therapymentioning
confidence: 99%